Aspects of the feeding ecology of three common Sparid fish in the littoral zone at Clayton's Rocks in the Eastern Cape, with notes on their biology - Christensen, Mikkel S (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1976)
The feeding interrelationships of three sparid fish was studied in the littoral zone during low tide at Clayton's Rocks in the Eastern Cape. The three species appeared in the study area only when between 9 and 10 mm long (SL), and remained resident until a length of approximately 120 fmm was reached. No sexually mature specimens occurred in the study area as large adults only use the intertidal zone for feeding purposes at high tide. From first recruitment into the littoral zone at 9 mm SL until some 35 mm long, the diet of Diplodus sargus consists of harpacticoid copepods and amphipods. Ingestion of amphipods and green algae increases with increased size of fish. Chironomid larvae, cirripede nauplii and an unidentifiable planktonic larva are important food items of small juveniles ( 50 mm), while diatoms are significant in larger juveniles (25 to 80 mm) in the spring/early summer season. The gut is short and the teeth are incisiform, backed by several rows of molars which increase in size and number with age. D.cervinus was almost completely carnivorous in the size range studied. The juveniles found on harpacticoid copepods and chironomid larvae while between 10 and 20 mm long. The diet then consists mainly of the shrimp Palaemon pacificus until the fish are 50 mm long and then amphipods until 100 mm long. All fish larger than this feed prodominantly on polychaetes. The gut is short and the teeth are similar to those of Q. sargus although there are fewer molars. From its first appearance at 10 mm, Sarpa salpa feeds mainly on harpacticoid copepods until 25 mm long. Diatoms then predominate in the diet, red algae also being taken until 75 mm long. Larger size classes are herbivores, feeding almost equally on red and green algae. Corresponding changes in gut length and dentition are reported, juveniles having a short gut and conical teeth and adults a long intestine and cuspidate, incisiform teeth. Marked ecological separation was observed between the three species. Spatial, temporal , behavioural and dietary differences were found . Q. sargus has continuous recruitment of juveniles into the littoral zone, S..salpa appears between July and early September and Q.cervinus is recruited from late September to November. Competition between small juveniles is reduced by cyclic abundances of food items important to each species and the sub-adults feed on different foods. Some competition exists between large juveniles of Q. sargus and Q.cervinus, but separation is maintained as individuals of the two species feed at different levels of the water column and in different parts of the littoral zone.
Keywords: Sparidae -- Physiology; Sparidae -- Ecology